Dermatomyositis paraneoplastic syndrome before symptomatic tonsillar squamous cell carcinoma: A case report. Issue 1 (27th June 2014) - Adi, Ahmad H.; Alturkmani, Hani; Spock, Todd; Williams Yohannes, Patrice; Wargo, Susannah; Szabo, Eva; Gutkind, J. Silvio; Van Waes, Carter; Andersen, Peter
Abstract Background Paraneoplastic syndromes are systemic or organ‐related functional tumor‐associated changes that arise distant to the tumor. Methods and Results We present a rare case of a 63‐year‐old man with dermatomyositis as a paraneoplastic syndrome developing more than a year before clinical manifestations of tonsillar squamous cell carcinoma (SCC). He subsequently developed stage T1N2bM0 IVA tonsillar SCC. He was treated on a research protocol with 3 weeks of neoadjuvant rapamycin therapy before right transoral lateral pharyngectomy and modified radical neck dissection with preservation of CN XI. His symptoms of dermatomyositis subsequently improved and he was weaned off immunosuppressive therapy. Conclusion To our knowledge, this is the first report of dermatomyositis as a paraneoplastic syndrome of tonsillar SCC in North America. We suggest that clinicians should monitor for signs of persistent or recurrent dermatomyositis symptoms as this may herald development or a return of the underlying malignancy. © 2014 Wiley Periodicals, Inc. Head Neck37: E1–E3, 2015